Morphological characteristics of judo cadets with respect to sex-related differences and athletic achievements - Nikolova, A.; Dimitrova, D. (Biomedical Human Kinetics, 2018)
Study aim: Understanding the morphological determinants of performance is important for talent identification and optimization of training programs. The aim of this study was to examine the morphological characteristics of male and female cadet judokas considering the sex-related differences and athletic achievements. Material and methods: Seventy-four (30 female and 44 male) cadet judokas from the Bulgarian National Team underwent an anthropometric assessment of height, weight, lengths, circumferences, and 8 skinfolds. Body fat percentage (%BF) was calculated using Slaughter et al. skinfold equations. Absolute and relative muscle mass, and arm and thigh muscle circumferences were also evaluated. Results: Except for the lower limb circumferences and thigh muscle circumference, a significant difference in most body dimensions was observed between the sexes. Male cadets had lower body fatness, but greater muscle mass as compared to female cadets. Medal winners from both sexes had lower %BF as compared to non-medalists. Male judokas with higher athletic achievements were significantly taller and had a larger arm span than their counterparts who are non-medalists (p < 0.05). Conclusions: Identified apparent sex-specific differences in almost all anthropometric variables and body composition parameters in adolescent judo cadets followed the pattern typical for adult athletes. Both male and female medal-winner cadets had lower %BF compared to the less successful athletes, but did not differ from them in the absolute and relative muscle mass and limb muscle circumferences. Our results suggest that maintenance of low body fat rather than higher muscle mass is essential for the competitive success of judo players.